First de novo KCND3 mutation causes severe Kv4.3 channel dysfunction leading to early onset cerebellar ataxia, intellectual disability, oral apraxia and epilepsy - Smets, Katrien (BMC Med Genet, 2015)
BACKGROUND: Identification of the first de novo mutation in potassium voltage-gated channel, shal-related subfamily, member 3 (KCND3) in a patient with complex early onset cerebellar ataxia in order to expand the genetic and phenotypic spectrum. METHODS: Whole exome sequencing in a cerebellar ataxia patient and subsequent immunocytochemistry, immunoblotting and patch clamp assays of the channel were performed. RESULTS: A de novo KCND3 mutation (c.877_885dupCGCGTCTTC; p.Arg293_Phe295dup) was found duplicating the RVF motif and thereby adding an extra positive charge to voltage-gated potassium 4.3 (Kv4.3) in the voltage-sensor domain causing a severe shift of the voltage-dependence gating to more depolarized voltages. The patient displayed a severe phenotype with early onset cerebellar ataxia complicated by intellectual disability, epilepsy, attention deficit hyperactivity disorder, strabismus, oral apraxia and joint hyperlaxity. CONCLUSIONS: We identified a de novo KCND3 mutation causing the most marked change in Kv4.3’s channel properties reported so far, which correlated with a severe and unique spinocerebellar ataxia (SCA) type 19/22 disease phenotype.